Burst-like superelasticity and elastocaloric effect in [011] oriented Ni50Fe19Ga27Co4 single crystals. (May 2018) - Zhao, Dewei; Xiao, Fei; Nie, Zhihua; Cong, Daoyong; Sun, Wen; Liu, Jian
Abstract: We have investigated the superelastic behavior and elastocaloric effect in [011] oriented Ni50 Fe19 Ga27 Co4 single crystals. The superelasticity is absent in a temperature gap of 60 K. At the critical temperature of 388 K, the stress oscillation and audible noise can be found during the superelastic deformation, indicating the occurrence of burst-like transformation. Such a burst character leads to a novel non-linear increase of martensitic transformation start stress with temperature, and an enhanced hysteresis loss. In addition, a large elastocaloric temperature window of 40 K and a maximum cooling effect of −6.1 K have been obtained. Graphical abstract: Unlabelled Image